2018
DOI: 10.1111/1365-2664.13193
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of pesticides on learning and memory in bees

Abstract: Most insecticides are insect neurotoxins. Evidence is emerging that sublethal doses of these neurotoxins are affecting the learning and memory of both wild and managed bee colonies, exacerbating the negative effects of pesticide exposure and reducing individual foraging efficiency.Variation in methodologies and interpretation of results across studies has precluded the quantitative evaluation of these impacts that is needed to make recommendations for policy change. It is not clear whether robust effects occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
128
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 84 publications
(142 reference statements)
6
128
2
2
Order By: Relevance
“…Therefore, if pesticide exposure were to affect early brain growth, by for instance reducing brain size, we might predict behavioural task performance, such as learning, to be impaired. However, while recognized as a research priority [32][33][34]45], no study to date has investigated how pesticide exposure during early-stage development affects brain developmental plasticity and its association with behavioural performance in older adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if pesticide exposure were to affect early brain growth, by for instance reducing brain size, we might predict behavioural task performance, such as learning, to be impaired. However, while recognized as a research priority [32][33][34]45], no study to date has investigated how pesticide exposure during early-stage development affects brain developmental plasticity and its association with behavioural performance in older adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Neonicotinoids target nicotinic acetylcholine receptors (nAChRs) which they bind to and thus excite; this can result in paralysis, convulsions and death (Matsuda et al, 2001). Controlled exposure experiments using honeybees and bumblebees have shown that exposure at comparable concentrations to those found in nectar and pollen can have sublethal effects on learning and memory (Siviter, Koricheva, Brown, & Leadbeater, 2018;Stanley, Smith, & Raine, 2015), cognition and problem solving (Baracchi, Marples, Jenkins, Leitch, & Chittka, 2017;Samuelson, Chen-Wishart, Gill, & Leadbeater, 2016;Williamson & Wright, 2013), motor function (Drummond, Williamson, Fitchett, Wright, & Judge, 2016;Williamson, Willis, & Wright, 2014), foraging performance (Gill & Raine, 2014;Henry et al, 2012;Stanley, Russell, Morrison, Rogers, & Raine, 2016), navigation abilities (Fischer et al, 2014) and the immune system (Brandt, Gorenflo, Siede, Meixner, & Büchler, 2016;Brandt et al, 2017;Di Prisco et al, 2013). Despite the growing interest in the link between neonicotinoid exposure and toxicity to bees, we know little about the molecules and genes through which neonicotinoid action is mediated, or whether neonicotinoids may also affect "off-target" processes that are not mediated by nAChRs.…”
mentioning
confidence: 99%
“…Sublethal health effects can translate into more dramatic effects, for example by increasing disease susceptibility [4,[7][8][9][10][11][12][13] or decreasing tolerance towards other stressors, such as land use intensification [14][15][16][17]. In addition, such pollutants are known to negatively affect learning abilities and/or lower activity levels [18][19][20][21][22][23][24], which may compromise insects even further [19,21,25].…”
Section: Introductionmentioning
confidence: 99%